2020
DOI: 10.1177/2309499019896237
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postoperative acute kidney injury after hip fractures in elderly patients

Abstract: Objectives: Acute kidney injury (AKI) is a rare but serious complication after hip fractures. The aim of this study was to evaluate the incidence and the risk factors of postoperative AKI after hip fractures. Methods: From January 2011 to December 2016, 550 patients who underwent surgery of hip fractures at our institution were retrospectively reviewed. AKI was defined and classified by AKI Network (AKIN) Classification/Staging System. The incidence, mortality, and risk factors of postoperative AKI were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
5
22
1
Order By: Relevance
“…Although the pre-surgery hemoglobin level was similar in both groups, the hemoglobin loss was more significant in the IR group. Previous studies have shown that perioperative blood loss is associated with lower mobility during physiotherapy ( 26 ), an increased risk for major adverse cardiovascular events ( 27 ), acute kidney injury ( 28 ), a longer hospital stay, and a higher rate of rehospitalization ( 29 ). Impaired kidney function tests, which were more common in the IR group, have a strong association with functional status in the future ( 30 , 31 ), a greater risk of major adverse cardiovascular events ( 27 ), and even increased mortality ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pre-surgery hemoglobin level was similar in both groups, the hemoglobin loss was more significant in the IR group. Previous studies have shown that perioperative blood loss is associated with lower mobility during physiotherapy ( 26 ), an increased risk for major adverse cardiovascular events ( 27 ), acute kidney injury ( 28 ), a longer hospital stay, and a higher rate of rehospitalization ( 29 ). Impaired kidney function tests, which were more common in the IR group, have a strong association with functional status in the future ( 30 , 31 ), a greater risk of major adverse cardiovascular events ( 27 ), and even increased mortality ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicated and irrelative items, the full texts of 57 remaining articles were screened for possible eligibility. Eventually, a total of 11 studies with 16,421 patients was included in the current meta-analysis [3,6,8,[16][17][18][19][20][21][22][23]. The flow chart of study selection was summarized in Figure 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…13,17,18 However, given that the clinical importance of a perioperative decrease in serum albumin levels or early postoperative hypoalbuminaemia on postoperative morbidities has been emphasized, it is important to concentrate on perioperative or early postoperative changes in serum albumin levels and their relationship with postoperative outcomes. [19][20][21][22][23][24] Several reports demonstrated the relationship between perioperative changes in serum albumin and the development of postoperative pneumonia in patients with gastric, colorectal, and lung cancers. 19,21,22,24 However, scant studies investigated the risk factors of postoperative pneumonia in patients undergoing hip fracture surgery, and the relationship between early postoperative hypoalbuminaemia and postoperative pneumonia has never been delineated.…”
Section: Introductionmentioning
confidence: 99%